Estimating ecological flows for fish overwintering in plain rivers using a method based on water temperature and critical water depth. Issue 5 (14th May 2019) - Wang, Li; Mo, Kangle; Chen, Qiuwen; Zhang, Jianyun; Xia, Jun; Lin, Yuqing
Abstract: Ecological flow is the foundation for conservation of riverine fish habitat and ecosystem. Habitat models have been widely used to estimate ecological flow owing to their integration of hydrological regime and species hydraulic preference. Previous studies based on habitat methods focused more on the spawning season but paid less attention to the winter period, which is also essential to fish life stage. This study developed a novel approach to estimate the ecological flow for fish overwintering, particularly in plain rivers. The water depth for target fish safely overwintering was firstly determined based on the minimum tolerable water temperature of the species. A water balance model was built to estimate the ecological flow for securing the determined water depth. The developed approach was applied in the middle reaches of Huaihe River, where the flow is highly regulated by dams and sluices. Parabramis pekinensis was selected as the target fish, and the minimum water depth for it to overwinter in the river was about 20 m. The calculated ecological flow was 3.0 m 3 ·s −1 in December, 2.2 m 3 ·s −1 in January, and 2.1 m 3 ·s −1 in February, respectively. The approach contributed a great supplement to fish spawning habitat model, and their combination could determine ecological flow regimes for the entire life cycle of the target fish.